Efficient waterproof grouting material and preparation method thereof
By adding specific components to polyurethane grouting materials and following specific treatments to form a dense physical structure, the problem of poor waterproofing performance of grouting materials in the prior art is solved, efficient waterproofing and good comprehensive performance are achieved, while ensuring the material safety and environmental protection.
Patent Information
- Application Number
- CN202411597843.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing polyurethane grouting materials have shortcomings in waterproofing performance, and ingredients that are harmful to the human body and the environment need to be added to improve waterproofing performance.
A highly efficient waterproof grouting material is adopted, and its composition includes hydroquinol, acrylic acid, methacrylic acid, magnesium oxide, calcined kaolin, heavy calcium carbonate, N-hydroxyethylacrylamide, N-hydroxymethylylacrylamide, Methacrylate derivatives, defoaming agents and dispersants are prepared by specific mixing and stirring processes to form a dense physical structure to improve waterproofing properties.
After curing, the material forms a dense physical structure, which significantly improves the waterproofing and comprehensive performance of the grouting material. It also has good chemical resistance and long-term stability, and the ingredients are non-toxic and do not harm the human body and the environment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting material preparation, and in particular to a high-efficiency waterproof grouting material and a preparation method thereof. Background Art
[0002] With the rapid development of my country's economy, energy shortage has prompted the vigorous development of coal mining industry. A number of large-scale, high-yield and high-efficiency underground mines have been put into production. The depth of traditional coal mines has increased, but it has also brought a series of problems. In many underground projects, concrete is prone to defects and cracks due to various stresses during long-term use, which greatly reduces the mechanical properties and causes significant losses to the national economy.
[0003] Due to its superior performance, polyurethane grouting materials are increasingly widely used in water conservancy, hydropower, tunnels, subways, mines, civil air defense, industrial and civil construction projects, especially in foundation reinforcement, leak stoppage, curtain anti-seepage and crack repair in engineering construction.
[0004] Document CN92106672.4 discloses a method for preparing polyurethane type grouting material, which is to use isocyanate residual liquid and hydroxyl compound as two components, directly and evenly mix them according to proportion, and then grouting is performed, and then cured at room temperature for use. The hydroxyl compound component can be used as a single component, or it can be used as the main body and various auxiliary agents or additives are added to share. These hydroxyl compounds can be polyether, polyester, polybutadiene, alkyd resin, polyacrylic resin, etc. The waterproof performance of the obtained grouting material is poor. Document CN200810052170.9 discloses a method for preparing a polyurethane chemical grouting single liquid grouting chemical material, but its preparation process is divided into three steps, first preparing a hydroxyl-terminated polyurethane prepolymer, then preparing a hydrophilic polyurethane prepolymer with it as a raw material, and finally adding a diluent, a foam stabilizer, a catalyst and a plasticizer to the hydrophilic polyurethane prepolymer in step 2 and stirring evenly to prepare it. The process is long and complicated, and the product contains a large amount (more than 20%) of low-boiling point solvent acetone, and acetone is a restricted chemical, which not only greatly reduces the safety of the product, but also puts forward extremely high qualification requirements for the manufacturer's raw material procurement and product transportation. At the same time, the cost is high and the waterproof performance is average. Document CN200910101168.0 discloses a high flash point (flash point>100°C) environmentally friendly water-soluble polyurethane chemical grouting material. It is characterized by being composed of isocyanate, hydrophilic polyether, plasticizer, high boiling point composite solvent (mixture of composite fatty acid esters) and foam stabilizer. It is suitable for anti-seepage treatment of dams and other building foundations, subways, tunnels, etc. The addition of the solvent at the end of the preparation process requires the addition of high boiling point solvent and foam stabilizer after the prepolymer reaction is completed, and its waterproof performance is average.
[0005] As can be seen from the above, the polyurethane grouting materials in the prior art all need to add ingredients that are harmful to the human body and the environment to improve their waterproof performance, and the waterproof performance is poor. Therefore, it is of great practical significance to provide a grouting material that can be highly effective in waterproofing. Summary of the invention
[0006] The purpose of the present invention is to provide a high-efficiency waterproof grouting material and a preparation method and application thereof, aiming to solve the technical problems of poor waterproof performance and poor comprehensive performance of the grouting material in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a high-efficiency waterproof grouting material, comprising the following components in parts by weight:
[0009] 0.5 parts of hydroquinone, 188 parts of acrylic acid, 20 parts of methacrylic acid, 84 parts of magnesium oxide, 150 parts of calcined kaolin, 225 parts of heavy calcium carbonate, 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 6 parts of butyl acrylate, 12 parts of diethylenetriamine, 50 parts of methacrylate derivatives, 2 parts of defoaming agent and 3 parts of dispersant.
[0010] Furthermore, the methacrylate derivatives are methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide.
[0011] Furthermore, the usage ratio of methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide is 1:2:2.
[0012] Furthermore, the defoamer is a mineral oil defoamer.
[0013] Furthermore, the dispersant is polycarboxylate ammonium salt.
[0014] The present invention also provides a method for preparing the high-efficiency waterproof grouting material described in the above technical solution, comprising the following steps:
[0015] Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture:
[0016] Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture;
[0017] adding N-hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, a methacrylate derivative and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture;
[0018] Adding a dispersant, a defoamer, calcined kaolin and heavy calcium carbonate to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material;
[0019] in:
[0020] The first mixing time is 4 to 6 hours, and the temperature is 50 to 60°C;
[0021] The second mixing time is 5 to 6 hours, and the temperature is 30 to 50°C.
[0022] Furthermore, the particle size of the calcined kaolin is 1000-1200 meshes.
[0023] Furthermore, the particle size of the heavy calcium carbonate is 800-1000 mesh.
[0024] The present invention also provides the use of the high-efficiency waterproof grouting material described in the above technical solution or the high-efficiency waterproof grouting material obtained by the preparation method in tunnel engineering or basement.
[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0026] The grouting material of the present invention is added with methacrylate derivatives, so that the obtained grouting material can be quickly cured when used, and a dense physical structure is generated after curing, thereby improving the strength and hardness of the grouting material. The dense physical structure greatly improves the waterproof performance of the grouting material; at the same time, the methacrylate derivative can be bonded with other added components to form a tight combination, and then a denser physical structure can be formed when used, so as to achieve the purpose of high-efficiency waterproofing, and the performance can maintain long-term stability; in addition, the grouting material obtained by the present invention has good chemical resistance to most acids and alkalis, is not affected by biological damage, and at the same time, the added components are non-toxic and will not harm the human body and the environment. DETAILED DESCRIPTION
[0027] The present invention provides a high-efficiency waterproof grouting material, comprising the following components in parts by weight:
[0028] 0.5 parts of hydroquinone, 188 parts of acrylic acid, 20 parts of methacrylic acid, 84 parts of magnesium oxide, 150 parts of calcined kaolin, 225 parts of heavy calcium carbonate, 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 6 parts of butyl acrylate, 12 parts of diethylenetriamine, 50 parts of methacrylate derivatives, 2 parts of defoaming agent and 3 parts of dispersant.
[0029] In the present invention, the methacrylate derivative is preferably methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide.
[0030] The present invention adopts the above-mentioned methacrylate derivatives so that the obtained grouting material can be quickly cured when used, and a dense physical structure is generated after curing, thereby improving the strength and hardness of the grouting material. The dense physical structure greatly improves the waterproof performance of the grouting material; at the same time, the methacrylate derivatives can be bonded with other added components to form a tight combination, and then a denser physical structure can be formed when used, thereby achieving the purpose of efficient waterproofing.
[0031] In the present invention, the usage ratio of methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide is preferably 1:2:2.
[0032] In the present invention, the defoaming agent is preferably a mineral oil defoaming agent.
[0033] The present invention does not specifically limit the specific type of the mineral oil defoamer, and any type familiar to those skilled in the art can be used. The present invention adds a mineral oil defoamer to make the resulting grouting material have excellent high temperature resistance and strong acid and alkali resistance, and can play a role in various complex production environments. Whether it is at a high temperature of more than 200 degrees or in an acid-base system environment of about 20%, it can maintain a stable foam control effect.
[0034] In the present invention, the dispersant is polycarboxylate ammonium salt.
[0035] The present invention preferably uses polycarboxylate ammonium salt as the dispersant of the present invention, weakening and breaking up the clustering connection between particles in the grouting material, releasing free water, thereby changing the properties of the hydration product and dispersing the particles; the addition of the dispersant in the present invention can reduce the plastic viscosity and yield value of the grouting material, which is beneficial to the flow and construction of the grouting material. By reducing the viscosity, the grouting material can more easily fill the structural gaps to form a dense and uniform grouting layer, thereby improving the waterproof effect. The present invention does not specifically limit the type of polycarboxylate ammonium salt, and those familiar to those skilled in the art can be used. In the embodiment of the present invention, polycarboxylate ammonium salt dispersant 5027 is used.
[0036] The present invention also provides a method for preparing the high-efficiency waterproof grouting material described in the above technical solution, comprising the following steps:
[0037] Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture:
[0038] Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture;
[0039] adding N-hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, a methacrylate derivative and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture;
[0040] Adding a dispersant, a defoamer, calcined kaolin and heavy calcium carbonate to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material;
[0041] in:
[0042] The first mixing time is 4 to 6 hours, and the temperature is 50 to 60°C;
[0043] The second mixing time is 5 to 6 hours, and the temperature is 30 to 50°C.
[0044] When the raw materials are mixed in the present invention, water is used for mixing and stirring. The amount of water used in the first mixing is preferably 306 parts.
[0045] In the present invention, the particle size of the calcined kaolin is preferably 1000-1200 mesh, and more preferably 1000-1100 mesh.
[0046] In the present invention, the particle size of the heavy calcium carbonate is preferably 800-1000 mesh, and more preferably 800-900 mesh.
[0047] The present invention also provides the use of the high-efficiency waterproof grouting material described in the above technical solution or the high-efficiency waterproof grouting material obtained by the preparation method in tunnel engineering or basement.
[0048] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0049] Example 1
[0050] (1) adding 0.5 parts of hydroquinone, 6 parts of butyl acrylate, 20 parts of methacrylic acid, 188 parts of acrylic acid and 306 parts of water into a reaction kettle, mixing them, maintaining the mixing temperature at 50° C., and stirring for 4 hours to obtain a first mixture;
[0051] (2) slowly adding 84 parts of magnesium oxide to the first mixture and stirring for 5 hours to obtain a second mixture, and controlling the temperature of the reactor to be 30° C. during the addition of magnesium oxide;
[0052] (3) adding 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 10 parts of methyl methacrylate, 20 parts of 2-aminoethyl methacrylate, 20 parts of methacrylate polyethylene glycol azide and 12 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;
[0053] (4) Add 3 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of mineral oil defoamer, 150 parts of calcined kaolin and 225 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1000 mesh, and the heavy calcium carbonate has a particle size of 800 mesh. After uniform mixing, the high-efficiency waterproof grouting material is obtained.
[0054] Example 2
[0055] (1) adding 0.5 parts of hydroquinone, 6 parts of butyl acrylate, 20 parts of methacrylic acid, 188 parts of acrylic acid and 306 parts of water into a reaction kettle, mixing them, maintaining the mixing temperature at 50° C., and stirring for 6 hours to obtain a first mixture;
[0056] (2) slowly adding 84 parts of magnesium oxide to the first mixture and stirring for 6 hours to obtain a second mixture, and controlling the temperature of the reactor to be 50° C. during the addition of magnesium oxide;
[0057] (3) adding 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 10 parts of methyl methacrylate, 20 parts of 2-aminoethyl methacrylate, 20 parts of methacrylate polyethylene glycol azide and 12 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;
[0058] (4) Add 3 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of mineral oil defoamer, 150 parts of calcined kaolin and 225 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1100 mesh, and the heavy calcium carbonate has a particle size of 900 mesh. After uniform mixing, the high-efficiency waterproof grouting material is obtained.
[0059] Example 3
[0060] (1) adding 0.5 parts of hydroquinone, 6 parts of butyl acrylate, 20 parts of methacrylic acid, 188 parts of acrylic acid and 306 parts of water into a reaction kettle, mixing them, maintaining the mixing temperature at 50° C., and stirring for 4 hours to obtain a first mixture;
[0061] (2) slowly adding 84 parts of magnesium oxide to the first mixture and stirring for 5 hours to obtain a second mixture, and controlling the temperature of the reactor to be 50° C. during the addition of magnesium oxide;
[0062] (3) adding 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 10 parts of methyl methacrylate, 20 parts of 2-aminoethyl methacrylate, 20 parts of methacrylate polyethylene glycol azide and 12 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;
[0063] (4) Add 3 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of mineral oil defoamer, 150 parts of calcined kaolin and 225 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1200 mesh, and the heavy calcium carbonate has a particle size of 1000 mesh. After uniform mixing, the high-efficiency waterproof grouting material is obtained.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-efficiency waterproof grouting material, characterized in that: The composition includes the following components in parts by weight: 0.5 parts of hydroquinone, 188 parts of acrylic acid, 20 parts of methacrylic acid, 84 parts of magnesium oxide, 150 parts of calcined kaolin, 225 parts of heavy calcium carbonate, 2 parts of N-hydroxyethyl acrylamide, 18 parts of N-hydroxymethyl acrylamide, 6 parts of butyl acrylate, 12 parts of diethylenetriamine, 50 parts of methacrylate derivatives, 2 parts of defoaming agent and 3 parts of dispersant.
2. The high-efficiency waterproof grouting material according to claim 1, characterized in that: The methacrylate derivatives are methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide.
3. The high-efficiency waterproof grouting material according to claim 2, characterized in that: The usage ratio of methyl methacrylate, 2-aminoethyl methacrylate and methacrylate polyethylene glycol azide is 1:2:
2.
4. The high-efficiency waterproof grouting material according to claim 1, characterized in that: The defoamer is a mineral oil defoamer.
5. The high-efficiency waterproof grouting material according to claim 1, characterized in that: The dispersant is polycarboxylate ammonium salt.
6. The method for preparing the high-efficiency waterproof grouting material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture: Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture; adding N-hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, a methacrylate derivative and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture; Adding a dispersant, a defoamer, calcined kaolin and heavy calcium carbonate to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material; in: The first mixing time is 4 to 6 hours, and the temperature is 50 to 60°C; The second mixing time is 5 to 6 hours, and the temperature is 30 to 50°C.
7. The method for preparing a high-efficiency waterproof grouting material according to claim 6, characterized in that: The particle size of the calcined kaolin is 1000-1200 meshes.
8. The method for preparing a high-efficiency waterproof grouting material according to claim 6, characterized in that: The particle size of the heavy calcium carbonate is 800-1000 meshes.
9. Use of the high-efficiency waterproof grouting material according to any one of claims 1 to 5 or the high-efficiency waterproof grouting material obtained by the preparation method according to any one of claims 6 to 8 in tunnel engineering or basement.
Citation Information
Patent Citations
Polyurethane chemical grouting material and production method
CN101220203B
High flashing point environment-friendly soluble polyurethane chemical grouting material
CN101613454A
Production of chemical grouting material from isocyanate residue
CN1036277C